Use of garlic in feed and water influence growth performances of broiler - M. E. Hossain (Journal of Agriculture, Food and Environment, 2020)
The aim of the investigation was to observe the effect of administration methods of garlic on productivity of broiler chickens.Three hundred and forty unsexed one-day-old broiler chicks were reared for 35 days. Chicks were assigned into five treatment groups, each treatment consistedof four replicates andeach replicate contained 17 birds. The dietary groups were; control (basal diet; no additives), antibiotic (basal diet + antibiotic), garlic-0.25% (basal diet + 0.25% garlic powder), garlic-0.50% (basal diet + 0.50% garlic powder) and garlic in water (basal diet + 1 colveof garlic/2 lit drinking water).The experimental diets were consisted of broiler starter (0-21 days) and broiler grower (22-35 days). Body weight, body weight gain, feed intake and feed conversion ratio of the birds were recorded every week. Results of this experiment indicate that supplementation of garlic in broiler diets significantlyeffect overall growth performances. Additionof garlic inwater showed higher (P<0.05) body weight as such as antibiotic and control groups compare to the garlic in feed groups. Data revealed that total feed intake in different dietary levels showed significant (P<0.05) difference. Control group showed significantly the higher feed intake over the other dietary groups. Improved (P<0.05) total feed conversion ratio was observed in garlic in water group as such as antibiotic group compare to the garlic in feed and control groups. However, feed conversion ratios in other weeks were not significant among treatments. These results suggest thataddition of garlic with feed has little or no effect on growth performances. However, body weight and feed conversion ratio were significantly influenced by water based infusion of garlic. As garlic contains various bioactive components, it couldbe a potential feed additive in broiler diet.